Digital Transformation of MP-ASI Education for Cadres (DIKADER) at Kramat Jati Community Health Center: Effectiveness Analysis - Ika Nopa; Antik Rachmawati P; Haris Iriyanto; Dita Eka Windiarti; Yunita Wulandari (Universitas Muhammadiyah Malang, 2026)
To reduce the prevalence of stunting, the Kramat Jati Community Health Center initiated and implemented the Digitalization of Education for Cadres (DIKADER) to improve cadres' knowledge of complementary feeding materials. This study aimed to measure the effectiveness of DIKADER as an educational method. Method: The research design was a pre-experimental, one-group, pretest-posttest design. The sample included 24 posyandu cadres selected through purposive sampling. The intervention in this study was the educational method. This method was developed by considering the content of the material, the medium through which the message would be delivered, and how frequently the message would be delivered. adres’ knowledge was assessed using a G-form questionnaire before and after the intervention, while satisfaction was measured at the end. Data were analyzed using the Wilcoxon test. Results showed increased knowledge of complementary feeding after the intervention; although most cadres were pre-elderly. Conclusion: This study recommends the implementation of a blended learning method, in the form of providing material and practice questions during online sessions, and role-playing during offline sessions as an effort to increase the capacity of cadres.